2019
DOI: 10.1253/circj.cj-19-0158
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Effectiveness and Tolerability of Tolvaptan in Patients With Heart Failure ― Final Results of the Samsca Post-Marketing Surveillance in Heart Failure (SMILE) Study ―

Abstract: Background:In Japan, tolvaptan is indicated for patients with heart failure and volume overload who have inadequate response to other diuretics. In contrast to the USA and Europe, tolvaptan can be used in Japan in patients with normal sodium levels. Methods and Results:In this multicenter, non-interventional, post-marketing surveillance study, prospective data from 3,349 patients treated with tolvaptan over a 5-year period were analyzed to identify benefits and risks. By Day 2 of treatment, 76.9% of evaluable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 24 publications
5
25
0
1
Order By: Relevance
“…21) Moreover, a postmarket surveillance in Japan (n = 1057) found that high doses of tolvaptan were a possible risk factor for hypernatremia (!150 mEq/L), and lower initial doses of tolvaptan were recommended. 32) Our subgroup analysis showed that the degree of change in serum sodium level was greater in the high-dose group. Hence, better strategies for optimizing doses of tolvaptan remain a challenge.…”
Section: Discussionmentioning
confidence: 68%
“…21) Moreover, a postmarket surveillance in Japan (n = 1057) found that high doses of tolvaptan were a possible risk factor for hypernatremia (!150 mEq/L), and lower initial doses of tolvaptan were recommended. 32) Our subgroup analysis showed that the degree of change in serum sodium level was greater in the high-dose group. Hence, better strategies for optimizing doses of tolvaptan remain a challenge.…”
Section: Discussionmentioning
confidence: 68%
“…The SMILE study, a post-marketing surveillance of tolvaptan, demonstrated from data of consecutive patients who had received tolvaptan between 2011 and 2015, that 43.6% of patients continued tolvaptan therapy for over two weeks in real-world clinical practice [3]. Also, 48.6% were aged over 80 years.…”
Section: Long-term Tolvaptan Therapymentioning
confidence: 99%
“…Almost half of the patients receiving tolvaptan therapy are aged over 80 years old [3] and we should understand the efficacy and safety of tolvaptan therapy in this population. The subanalysis of SMILE study demonstrated that the effectiveness of tolvaptan therapy in patients aged over 80 years old was similar to that in younger patients [21].…”
Section: Elderly Populationsmentioning
confidence: 99%
See 2 more Smart Citations